Pengaruh Pemaparan Medan Magnet Pada Media Mandels Yang Dimodifikasi Terhadap Pertumbuhan Dan Aktivitas Enzim Selulase Bacillus Sp. - hernawati, wayan; sumardi, sumardi; agustrina, rochman; yulianto, herman (Politeknik Negeri Lampung., 2016)
Enzymes can undergo structural changes due to various environmental factor such as pH,temperature, electricity and magnetic fields. The purpose of this study was to investigate theeffect of magnetic field strength and duration of exposure to the modified of media Mandelsused as a culture medium of Bacillus sp. on the growth and activity of cellulase enzyme fromthe bacterium Bacillus sp. Factorial study group were prepared using the method of fullrandomized design (RKLT). The first factor is the strong magnetic field consists of 4 levels ofmagnetic field strength treatment: 0 mT; 0,1 mT; 0,2 mT; 0.3 mT. The second faktor is theprolonged exposure consisting of 4 levels prolonged exposure treatments 0, 10, 20, 30minutes. each unit treatment was repeated 3 times. The results showed that exposure tomagnetic fields on modified of media Mandels causes a decrease in the relative activity ofthe enzyme cellulase and relative growth of Bacillus sp.Keywords: cellulase enzyme, magnetic field, Mandels modification, Bacillus sp.